Coupling and Regulation of Porous Carriers Using Plasma and Amination to Improve the Catalytic Performance of Glucose Oxidase and Catalase - Liao, Lingtong; Meng, Yuling; Wang, Ruiming; Jia, Baolei; Li, Piwu (Frontiers in Bioengineering and Biotechnology, 2019)
Multiple enzymes systems are being used more widely for their high-efficiency. Co-immobilization would be the key technology to lower the cost and improve stability of the enzymes. In this study, poly glycidyl methacrylate (PGMA) spheres were synthesized using suspension polymerization, and were used as support with the aim of co-immobilizing glucose oxidase (GOx) and catalase (CAT). The surface modification was carried out via a combination of plasma and amination to promote the properties of the catalyzer. The co-immobilized enzymes showed a more extensive optimum pH and temperature from 5.5–7.5 and 25℃–40℃, respectively, than with free enzymes. Furthermore, the maximum activity and protein adsorption quantity of the co-immobilized enzymes reached 25.98 U/g and 6.07 mg/g, respectively. The enzymatic activity of the co-immobilized enzymes was maintained at approximately 70% after storage for 5 days and 82% after three consecutive cycles, which indicated that the immobilized material could be applied industrially.